Hermeneutika Double Movement Fazlur Rahman Dalam Studi Hadits - Yuniarti Amalia Wahdah (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
The stagnation that occurs in the study of hadith science causes Fazlur Rahman to offer a new methodology in understanding hadith, namely Double Movement hermeneutics. It includes two movements in which the first movement starts from the context of the present to the time of the hadith conveyed by the Prophet by studying textually as well as socio-historically. The second movement is to return to the present by applying the moral ideals implied in the hadith. The Prophet's comment in the hadith forbidding women's leadership is just a response to the Queen of Persia's appointment at the time, not a shar'i provision in choosing a leader, according to the Double Movement theory. So that nowadays women may be elected to serve as leaders on condition that they have adequate authority and leadership.